VARIASI EKSTRAK ETANOL BIJI KEBIUL (Caesalpinia bonduc (L). Roxb) PADA FORMULASI SEDIAAN EMULSI M/A - Densi Selpia Sopianti; Abdul Ricki; Aina Fatkil Haque (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2021)
Indonesia is an archipelago state that is the nature have provides raw materials from medicinal plants, it is not yet used cause medicinal plants usually lived in the forests that have difficult access. Kebiul seed (Caesalpinia bonduc (L.) Roxb.) is an empirically medicinal plant belonging to the Caesalpiniaceae family which has great potential to be used as an prevent from free radicals or as an antoxidants cause kebiul seeds contains alkaloids, flavonoids, saponins, and steroids.The aims of this research to make a M/A emulsion substance. The sample that have been used in this study is kebiul seeds that have extracated by maceration and then evaporated with a waterbath. The extract was made in four formulas with each concentration 10%, 20%, 30%. The evaluation of the M/A have perfect result which were done, stability test (odor, color and shape / texture and pH test) flow properties test, viscosity test, emulsion type test, and microscope cross-section test. After analyzing the M/A emulsion substance the results from all of the evaluations that have been done from the 4 formulas, the kebiul seeds could be made into M/A Emulsion. Variation in contents of Caesalpinia bonduc (L.) Roxb extract which have the requirements evaluation, namely: organoleptic test, pH test, stability test, emulsion type test, viscosity test, and microscope cross-section test.